Perpaduan Gaya Arsitektur Klasik dan Modern pada Bangunan Lawang Sewu Semarang - Khasan Azabit; Faiz Zulfikar (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
Lawang Sewu is one of the historic buildings that has become an icon in the city of Semarang that presents a blend of classical and modern architectural styles. Lawang Sewu is located in the center of Semarang City, precisely at Jalan Pemuda No. 160, Sekayu, Semarang Tengah District, Semarang City, Central Java. The Lawang Sewu area is one of the historic areas of the Dutch Colonial heritage. The Lawang Sewu building in Semarang displays a blend of classical architectural styles that can be seen in the building structure, elements such as typical Javanese carvings, and the use of materials such as teak wood, while the blend of modern architectural styles can be seen in the renovation and addition of modern elements such as white paint on the concrete pillars. Lawang Sewu has succeeded in uniting classical and modern architectural elements, thus creating an attractive building impression. This blend provides added value to this historic building, making it a tourist icon for visitors.